Phone Monitoring to Improve Service Delivery : A SIEF-Supported Nimble Evaluation in India - World Bank (World Bank, Washington, DC, 2019)
In many low-income countries, improving service delivery can be challenging, whether it's making sure that teachers are in the classroom ready to teach or that cash transfers reach intended beneficiaries. One reason is that it's often difficult to cost-effectively monitor programs, especially when they cover thousands of communities and include very remote areas. This was the challenge faced by the Indian state of Telangana when it introduced a new program to make payments to farmers to help them buy seeds and fertilizer before each of the two major planting seasons. The government wanted to ensure that people received their money in the expected time frame and that farmers were not asked to make any payments for receiving their money. Intervention. Under the state's new Rythu Bandhu (Friend of the Farmer) program, landholding farmers are supposed to receive the equivalent of about 55 US Dollars per acre before the summer and winter planting seasons. About 5.7 million farmers qualified and close to 90 percent of them owned less than three acres. The first distribution was made before the 2018 summer planting season. Beneficiaries were given checks that could be exchanged for cash at a local bank, regardless of whether a person had a bank account. The checks were distributed during village meetings organized by the state's agricultural officer in each subdistrict, known as a mandal, who supervised agricultural workers sent to villages to deliver checks.